Broughton, Clay County - Morgan, M.J. (Kansas State University, The Chapman Center for Rural Studies, 2012)
At the latest estimate, Kansas may have nearly 9,000 vanished, named communities. These places had many faces: small crossroads villages; depot mail drops on rail lines, lingering communities that coalesced around a church, rapidly-fading religious colonies on the bleak western plains; villages that grew up on both sides of a river; towns that had as many as five names -- and towns that had a single name but no people. Vanished town signs state proudly that here was the first orphanage, denominational church, ladies’ institute, Pony Express stop, mission, or trading post. Regardless of how these towns are remembered, and for what, they are all related in one way: they were someone’s home town.
M.J. Morgan, Research Director , “Broughton, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/35.
Keywords: Broughton; Chapman; Clay County; Milford Dam Constuction; Pony Express Stop; Republican River